A double‐blinded randomized multicentre study to investigate the effect of changes in stimulation parameters on sacral nerve stimulation for constipation. (November 2015) - Thomas, G. P.; Duelund‐Jakobsen, J.; Dudding, T. C.; Bradshaw, E.; Nicholls, R. J.; Alam, A.; Emmanuel, A.; Thin, N.; Knowles, C. H.; Laurberg, S.; Vaizey, C. J.
Abstract Aim Sacral nerve stimulation (SNS) may be offered to patients with constipation who have failed to improve with conservative treatment. The response to SNS is variable, with a significant loss of efficacy in some patients. An increased frequency of stimulation may improve the efficacy of SNS for faecal incontinence. This study aimed to see if alteration of the pulse width or frequency improved the outcome for those with constipation. Method Eleven patients with constipation currently being treated by SNS were recruited from three centres. They were randomized to five different protocols of stimulation each applied for 5 weeks. Group 1 used standard settings (pulse width 210 μs, frequency 14 Hz); in the other four groups (Groups 2–5) the pulse width and/or frequency were halved or doubled. Patients and investigators were blinded to the group allocation. Results The Cleveland Clinic constipation score varied significantly between the five groups. Group 1 achieved the lowest score mean (± SD) 13.4 (± 4.4) (P = 0.03). The number of digitations per defaecation was the lowest in Group 4, 90 μs and 14 Hz (P < 0.01). No other variable changed significantly. Standard settings were the most preferred by the recruited patients. Conclusion Alteration of pulse width or frequency of stimulation had no significant effect on the outcome of SNS for constipation.